BMI-Associated Anti-Apolipoprotein A-1 Positivity in Healthy Adults after mRNA-Vaccination against COVID-19 - Máčalík, Roman; Petráš, Marek; Čelko, Alexander M; Chmátal, Petr; Tlapák, Jakub; Dlouhý, Pavel; Malinová, Jana; Lesná, Ivana Králová (Vaccines, 2023)
Elevated anti-apolipoprotein A-1 (AAA1) antibody levels associated with cardiovascular risk have been observed in previously SARS-CoV-2-infected or COVID-19-vaccinated individuals. Since patient safety is generally a priority in vaccination, we sought to investigate AAA1 antibody levels in healthy adults after mRNA vaccination. We conducted a prospective cohort study in healthy adult volunteers recruited from military workers of the Transport Air Base in Prague who had received two doses of mRNA vaccines. Anti-apolipoprotein A-1 antibody levels were determined using ELISA from serum samples obtained at three and four time points after the first and second vaccine doses, respectively, within almost 17 weeks of follow-up. The transient AAA1 positivity rate achieved 24.1% (95% confidence interval CI: 15.4-34.7%), i.e., 20 out of 83 participants had at least one positive post-vaccination sample, with a repeat positivity confirmed in only 5 of them. This rate was associated with a BMI > 26 kg/m2, as documented by an adjusted odds ratio of 6.79 (95% CI: 1.53-30.01). In addition, the highest positivity rate of 46.7% (21.3-73.4%) was observed in obese subjects with >30 kg/m2. Since the incidence rate of AAA1 positivity remained unchanged after the first and second vaccine doses, any relationship between AAA1 positivity and mRNA vaccination was inconclusive. The present study showed a transient AAA1 positivity rate associated with overweight or obesity without a proven association with mRNA vaccination.
Keywords: obesity; BMI; autoantibody; anti-apolipoprotein A-1; mRNA vaccination